Uncombable hair improved by biotin - Jakob L. Drivenes; Ramon Grimalt; Regina C. Betz; Anette Bygum (Wiley, 2023)
Abstract Uncombable hair syndrome (UHS) is a rare disorder of hair shaft morphology. UHS presents in early childhood with blonde, dry and frizzy scalp hair. The rate of hair growth may be normal or slow. The UHS hair shaft is characterized by a triangular shape with longitudinal grooves along the hair shaft axis. At writing, no curative treatment is available for UHS. However, research suggests that oral biotin supplementation results in a clinical improvement in growth rate and texture in some cases. Here, we present the case of a girl with UHS who was successfully treated with oral biotin supplementation. Our case highlights the diagnostic pathway in UHS, and demonstrates that two cycles of treatment with biotin, each separated by a period of 3 years, led to a significant improvement in combability and growth rate in a patient with UHS. We propose that biotin is a safe treatment option for UHS when both the health care provider and the family are aware of the possible interference with laboratory test results.